A longitudinal analysis of the differential performances of seeded male and female Grand Slam tennis players - Stefani, R. (The Sport Journal, 2020)
Purpose: This paper evaluates Grand Slam tennis at the most fundamental level, the match-by-match competition between established players and their challengers. The competitive balance of men and women therefore is evaluated in this paper, as measured by the success of lower-seeded or un-seeded competitors at winning matches. Methods: A 14-season database was tabulated, covering 56 Grand Slams for men and 56 for women contested from 2006 through 2019, including nearly 5,000 matches for men and 5000 for women, each involving at least one seeded player. Results and Discussion: Overall, higher seeded players were upset in 25% of women`s matches and in 21% of men`s matches. As an average season progressed, women were involved in more upset matches than men by 28% at the season opening Australian open on hard court, by 15% on red clay at the French Open, by 14% on grass at Wimbledon (where the most upsets happened for both men and women) ending with 11% on hard court at the US Open. Lower-seeded or un-seeded men became consistently more competitive as each season progressed, while women remained at the same highly competitive level. On a year-by-year basis, competitive balance (upsets) have increased somewhat, that is, the predictability of higher-seeded players has decreased over time. Conclusions: The cumulative effect of the upset differential is that spectators watched the progress of the strongest men`s seeds, wondering how they would do against the three dominant men`s players, Nadal, Djokovic, and Federer, who won 48 of the men`s 56 Grand Slams over the 14-year period. In contrast, dynamic new young female players emerged, winning by upset until some became higher seeds and even Grand Slam champions themselves, only to be upset and replaced as champion by a new wave of enthusiastic and compelling competitors, exemplified by the fact that 24 women won their 56 Grand Slams. Applications to Sport: The marketing, advertising, and psychological/physical player preparation should consider the fundamental spectator`s eye views that differentially define men and women`s Grand Slam tennis.